2022
DOI: 10.3390/microorganisms10061238
|View full text |Cite
|
Sign up to set email alerts
|

A Calculator for COVID-19 Severity Prediction Based on Patient Risk Factors and Number of Vaccines Received

Abstract: Vaccines have allowed for a significant decrease in COVID-19 risk, and new antiviral medications can prevent disease progression if given early in the course of the disease. The rapid and accurate estimation of the risk of severe disease in new patients is needed to prioritize the treatment of high-risk patients and maximize lives saved. We used electronic health records from 101,039 individuals infected with SARS-CoV-2, since the beginning of the pandemic and until 30 November 2021, in a national healthcare o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We identified two protective factors against serious illness: vaccination status and prior history of COVID-19 infection. Many of the risk factors that were identified here, such as age, gender, socioeconomic status, and comorbidities, have also been identified in other models that have been developed [ 8 , 9 , 10 , 11 , 14 , 15 , 16 ]. In another HMO-based Israeli study, the number of doses was found to have a protective effect against hospitalization and mortality.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We identified two protective factors against serious illness: vaccination status and prior history of COVID-19 infection. Many of the risk factors that were identified here, such as age, gender, socioeconomic status, and comorbidities, have also been identified in other models that have been developed [ 8 , 9 , 10 , 11 , 14 , 15 , 16 ]. In another HMO-based Israeli study, the number of doses was found to have a protective effect against hospitalization and mortality.…”
Section: Discussionmentioning
confidence: 86%
“…Israel et al also developed a scoring model including vaccination status. They already included four doses of vaccine [ 11 ] and evaluated similar variables as our study did. However, they only addressed the number of vaccines and not their timing and did not consider prior episodes of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Rationale . Age is one of the main prognostic factors of a poor clinical outcome (hospitalization, need for intensive care or death) in patients infected with SARS-CoV-2, with a strong association with the age of 65 years and a maximum from the age of 70 years onwards, both in unvaccinated and vaccinated populations [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ]. There is also a correlation between comorbidity and poorer clinical outcome, including mortality, at all ages, although particularly after 60 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…There is also a correlation between comorbidity and poorer clinical outcome, including mortality, at all ages, although particularly after 60 years of age. The strength of this association increases with the number of comorbidities affecting the patient, with the association being highest for three or more pathological processes, both in unvaccinated and vaccinated subjects, including pediatric patients [ 9 , 40 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. In nursing homes for older adults (NHOA), the factors associated with poorer clinical outcomes are age, health status and frailty [ 31 , 88 , 90 , 92 , 95 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation